2014
DOI: 10.1080/13691058.2014.968806
|View full text |Cite
|
Sign up to set email alerts
|

Identifying factors that influence pregnancy intentions: evidence from South Africa and Malawi

Abstract: In developing-country settings, pregnancy intentions are often assessed using a series of questions from the Demographic and Health Surveys, yet research conducted in several countries yields conflicting results regarding these questions' ability to predict pregnancy. Conducted in Malawi and South Africa, this study identified individual, partner and societal factors that influence desire for pregnancy, and women's ability to achieve their intentions. Data come from interviews and focus-group discussions condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 23 publications
4
24
0
Order By: Relevance
“…Similar to other studies in Malawi and other sub-Saharan countries, we found that having fewer children and partner’s desired fertility were associated with HIV-positive men and women desiring fertility [ 2 , 4 , 10 13 , 19 , 20 , 32 ]. Interestingly, age—which is inconsistently reported as associated with fertility intentions—was not associated with the desire for future children in our study.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar to other studies in Malawi and other sub-Saharan countries, we found that having fewer children and partner’s desired fertility were associated with HIV-positive men and women desiring fertility [ 2 , 4 , 10 13 , 19 , 20 , 32 ]. Interestingly, age—which is inconsistently reported as associated with fertility intentions—was not associated with the desire for future children in our study.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings may therefore not be generalizable outside of this group. The homogeneity of our participants in regards to ART use, being in committed relationships, and disclosing their status to partners also limited our ability to study these factors previously found to be related to desired fertility [ 2 , 10 , 11 , 18 , 19 , 32 ]. However, the two clinics provide HIV management for a large portion of HIV-positive people in Malawi’s capital.…”
Section: Discussionmentioning
confidence: 99%
“…[73] Finally, while the study provides some measure of unmet need for contraception, this indicator is hard to measure, and the variable used (unintended pregnancy) only provides limited information. [74,75]…”
Section: Researchmentioning
confidence: 99%
“…A study on pregnancy intentions in South Africa and Malawi among HIV-positive women and their partners, seroconcordant and serodiscordant, found that a partner's expectations for pregnancy, finances, and family composition were key factors in negotiating pregnancy desires. The majority of participants did not actively plan for a pregnancy and challenged the notion that reproductive decisions are always conscious actions [ 64 ]. Women's conscious decisions, cited in another study, were based on their judgment of the positive aspects of motherhood versus the negative pressures of social stigma [ 65 ].…”
Section: Resultsmentioning
confidence: 99%